La organización social del trabajo en los ingenios azucareros canarios (siglos XV-XVI). The Social Organization of Work in Sugar Mills of the Canary Islands (15th-16th centuries) - Viña Brito, Ana (En la España Medieval, 2006)
This study shows the characteristics of the population that worked in the plantations and sugar mills in the Canaries during the first century after colonization. The workforce comprised qualified personnel: technicians and officers, generally from Portugal or more specifically from Madeira, the general body of paid workers, basically colonists, and the slaves, mainly of African origin. We analyze the qualitative and quantitative importance of each of these groups, from the end of the fifteenth century until the middle of the sixteenth, in each of the four “sugar islands”. Although the slaves were a major part of the workforce, they were not much more numerous than free workers in the plantations and mills, in contrast to the situation in other Atlantic territories involved in the production of sugar.